Awareness of eye diseases in an urban population in southern India - Dandona Rakhi; Dandona Lalit; John Rajesh K.; McCarty Catherine A.; Rao Gullapalli N. (The World Health Organization, 2001)
OBJECTIVE: To assess the level of awareness of eye diseases in the urban population of Hyderabad in southern India. METHODS: A total of 2522 subjects of all ages, who were representative of the Hyderabad population, participated in the population-based Andhra Pradesh Eye Disease Study. Of these subjects, 1859 aged >15 years responded to a structured questionnaire on cataract, glaucoma, night blindness and diabetic retinopathy to trained field investigators. Having heard of the eye disease in question was defined as ??awareness?? and having some understanding of the eye disease was defined as ??knowledge??. FINDINGS: Awareness of cataract (69.8%) and night blindness (60.0%) was moderate but that of diabetic retinopathy (27.0%) was low, while that of glaucoma (2.3%) was very poor. Knowledge of all the eye diseases assessed was poor. Subjects aged > 30 years were significantly more aware of all eye diseases assessed except night blindness. Multivariate analysis revealed that women were significantly less aware of night blindness (odds ratio (OR) = 0.78; 95% confidence interval (CI) = 0.63-0.97). Education played a significant role in awareness of these eye diseases. Study subjects of upper socioeconomic status were significantly more aware of night blindness (OR = 2.20; 95% CI = 1.29-3.74) and those belonging to upper and middle socioeconomic strata were significantly more aware of diabetic retinopathy (OR = 2.79; 95% CI = 2.19-3.56). Muslims were significantly more aware of cataract (OR = 2.36; 95% CI = 1.84-3.02) and less aware of night blindness (OR = 0.52; 95% CI = 0.42-0.64). The major source of awareness of the eye diseases was a family member/friend/relative suffering from that eye disease. CONCLUSION: These data suggest that there is a need for health education in this Indian population to increase their level of awareness and knowledge of common eye diseases. Such awareness and knowledge could lead to better understanding and acceptance of the importance of routine eye examinations for the early detection and treatment of eye diseases, thereby reducing visual impairment in this population.